Digital literacies : social learning and classroom practices - Carrington, Victoria;Robinson, Muriel (Los Angeles, California : Sage Publications, Incorporation, 2009)
Digital technologies are an everyday part of life for students and this book explores the ways in which they can be used in schools. The authors provide insight into the research on digital technologies, stressing its relevance for schools, and suggest ways to develop new, more relevant pedagogies, particularly for social learning, literacy, and literate practices. With a practical focus, the examples and issues explored in this book will help you to analyze your own practice and to carry out your own small-scale research projects.
Introduction. Contentious Technologies - Part A. Digital texts in and out of school - 1. Young people's video productions as new sites of learning - 2. A space for play: crossing boundaries and learning online - 3. Masters and critics: children as producers of online digital texts - Part B. - Changing literacies - 4. From Wikipedia to the humble classroom Wiki : why we should pay attention to Wikis - 5. Negotiating the blogosphere: educational possibilities - 6. Virtual worlds in real-life classrooms - Part C: Changing literacies, changing pedagogies - 7. Personal digital literacies versus classroom literacies: investigating pre-service teachers' digital lives in and beyond the classroom -- Digital portraits: teacher education and multiliteracies pedagogy -- 8.Composing with old and new media: toward a parallel pedagogy Part D. Interconnectivity.
Includes bibliographical references and index.
Keywords: TEACHING -- COMPUTER NETWORK RESOURCES